Thermally-induced nonlinear optical properties of Ti-Al oxide nano-films with double epsilon-near-zero behavior - Husam H. Abu-Safe (1900318) (2021)
This research examines the thermally-induced nonlinear optical properties of Ti-Al-oxide nano-films. The Ti-Al nano-layer system was sequentially evaporated on glass and c-Si(100) substrates at room temperature. The Ti layers were spontaneously oxidized by the residual oxygen of the background vacuum in the deposition chamber. The Al layer, on the other hand, was partially oxidized and contained metallic inclusions. However, when oxygen was deliberately introduced into the chamber, the Al layer was oxidized with smaller inclusions. We experimentally demonstrate the existence of double epsilon-near-zero (2ENZ) behavior in the oxidized Al films by directly measuring the dielectric permittivity through ellipsometric analysis. The Maxwell-Garnett theory for a composite film formed by a mixture of Al and TiO2 inclusions in Ti-Al-oxide matrix was used to predict the two cross-over points of the ENZ behavior. Enhancement in the nonlinear optical response near the ENZ points was obtained. Other Information Published in: Optical Materials Express License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1364/ome.413972